The Priestly Identity of Melchizedek and the Messianic Views in the Testament of Levi and the Epistle to the Hebrews - CHEN, Yu (Journal of Research for Christianity in China (JRCC), 2026)
This paper provides a comparative textual analysis of the Melchizedek priestly tradition and its messianic implications as presented in two key passages: Testament of Levi 18 and Hebrews 7. Despite their distinct literary genres, historical contexts, and theological purposes, both texts share a remarkably consistent theological framework. Each emphasizes a priestly office that is eternal and divinely ordained, transcending established levitical lineage; each bases its vision on a critique of the existing priestly system; and each intimately fuses priestly function with messianic expectation. Building on this common foundation, the Testament of Levi foregrounds the figure of a future “new priest”—a composite eschatological deliverer who acts as king, warrior, and judge, exercising authority in divine warfare and final judgment. Hebrews, in contrast, systematically develops the idea of Jesus Christ as the eternal high priest “after the order of Melchizedek.” Its argument culminates in the definitive, once-for-all efficacy of his sacrificial offering, raising the tradition to a Christological height centered on his unique person and work. The study demonstrates how these two writings, individually and in dialogue, bear witness to the fluidity and richness of messianic speculation in late Second Temple Judaism, particularly the emerging conception of a “priestly messiah.” Furthermore, it illuminates the early Christian movement’s creative reinterpretation of Jewish scriptural and interpretive traditions. Through its reshaping of the Melchizedek narrative, Hebrews articulates a coherent vision of Jesus Christ as the singular Savior, fulfilling both messianic hope and divine sonship.